Perspektif Perawat Ruangan tentang Caring dalam Merawat Pasien Kanker yang Menjalani Kemoterapi - Made Indra Ayu Astarini; M.T Arie Lilyana; Ninda Ayu Prabasari (Poltekkes Kemenkes Jakarta III, 2020)
Cancer patients undergoing chemotherapy have a certain degree of dependence. Nurses are present as service providers with caring experiences. Nurses' perception of caring is limited to the technical aspects of care. The purpose of this study is to explore nurse’s perspectives on caring behavior in treating cancer patients undergoing chemotherapy. The design of this study is a qualitative research. The participants were five nurses who directly involved in chemotherapy services. The sampling technique was purposive sampling. Data collection was carried by conducting in-depth interviews. The data collected were then analized according to the theme by Interpretative Phenomenological Analysis (IPA) and objectives of the study. This study has been approved in legal and ethic. Based on the results of the theme analysis, there are three themes namely caring understanding, forms of caring for cancer patients undergoing chemotherapy, and the benefits of caring. Nurses' perceptions about forms of caring behavior for cancer patients undergoing chemotherapy are establishing relationships, conducting assessments, providing care that patients need and providing education related to patient health. This study recommends to provide information for nurses about nurse caring behavior that can be applied to cancer patients undergoing chemotherapy, so that nurses can improve caring behavior in patients